The Role of Organizational Support in Enhancing Lecturer Performance: The Role of Commitment as a Mediator and Lecturer Certification as a Moderator - Syahsudarmi, Siti; Juniarti, Atty Tri; Setia, Bayu Indra (Almana : Jurnal Manajemen dan Bisnis, 2024)
This study aims to examine the influence of organizational support on the performance of lecturers, mediated by commitment, and moderated by lecturer certification. The research was conducted in the undergraduate program in the field of economics at private universities in Riau Province. The research method used was a survey with a questionnaire as the data collection instrument. The population and sample of the study consisted of 269 respondents. Data analysis was conducted using SEM-PLS. The results of the study indicate that organizational support has a significant effect on commitment. Organizational support also has a significant effect on performance, which is mediated by commitment. Furthermore, organizational support affects performance, which is mediated by commitment and moderated by lecturer certification. The implications of this research highlight the importance of private universities in Riau Province considering these factors in the management and development of human resources, especially lecturers, to improve the quality of education. This study provides theoretical and practical contributions to understanding the factors that influence lecturer commitment and performance.